Modelling of the Effect of Selenium Fertilization on the Content of Bioactive Compounds in Broccoli Heads - Mahn-Osses, A (Elsevier Ltd, 2017)
Selenium (Se) exerts many effects beneficial to health. Broccoli is a Se-hyperaccumulator plant, with Se-fertilization increasing its potential as a functional food. We studied the effect of dose, and the developmental stage at the beginning of Se-fortification, on antioxidant capacity, phenolics, glucosinolates, sulphoraphane, Se-methyl selenocysteine and myrosinase in broccoli. Se-fortification decreased the antioxidant properties and sulphur-containing compounds, but increased Se-methyl-selenocysteine content. Regression models gave r > 0.77 confirming that Se dose and developmental stage largely determine the behaviour of the system. Correlation models gave r > 0.95, allowing estimation of saturation concentration of Se-methyl-selenocysteine in broccoli cv. Traditional (3.13 µmol g−1 DM) and the concentration (2-mmol sodium selenate) above which the content of phenolic compounds decreases significantly. Sulphoraphane and glucosinolates’ dependence on total Se supply was consistent with myrosinase activity below 3.5-mmol sodium selenate. Our results would enable design of optimal fertilization strategies to enrich broccoli in Se with minimal impairment of antioxidants properties. © 2017 Elsevier Ltd
Keywords: Selenium; Se-methyl selenocysteine; Phenolic compounds; Myrosinase-glucosinolate system; Antioxidant capacity; Modelling